Controlling Thermal Expansion in Supramolecular Halogen‐Bonded Mixed Cocrystals through Synthetic Feed and Dynamic Motion. (21st April 2022) - Juneja, Navkiran; Shapiro, Nicole M.; Unruh, Daniel K.; Bosch, Eric; Groeneman, Ryan H.; Hutchins, Kristin M.
Abstract: Control over thermal expansion (TE) behaviors in solid materials is often accomplished by modifying the molecules or intermolecular interactions within the solid. Here, we use a mixed cocrystal approach and incorporate molecules with similar chemical structures, but distinct functionalities. Development of mixed cocrystals is at a nascent stage, and here we describe the first mixed cocrystals sustained by one‐dimensional halogen bonds. Within each mixed cocrystal, the halogen‐bond donor is fixed, while the halogen‐bond acceptor site contains two molecules in a variable ratio. X‐ray diffraction demonstrates isostructurality across the series, and SEM‐EDS shows equal distribution of heavy atoms and similar atomic compositions across all mixed cocrystals. The acceptor molecules differ in their ability to undergo dynamic motion in the solid state. The synthetic equivalents of motion capable and incapable molecules were systematically varied to yield direct tunabililty in TE behavior. Abstract : A strategy has been developed for controlling thermal expansion using a mixed cocrystal approach, wherein thermal expansion is tuned by controlling the synthetic feed and functionality of the halogen‐bond acceptor molecules. The appearance and composition of the bulk material is similar across the series, as evidenced by X‐ray diffraction and SEM‐EDS; however, expansion behaviors differ due to the dynamic motion ability of the acceptor molecules.